2015
DOI: 10.1038/srep09124
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing of case-unaffected-parents trios reveals recessive and de novo genetic variants in sporadic ALS

Abstract: The contribution of genetic variants to sporadic amyotrophic lateral sclerosis (ALS) remains largely unknown. Either recessive or de novo variants could result in an apparently sporadic occurrence of ALS. In an attempt to find such variants we sequenced the exomes of 44 ALS-unaffected-parents trios. Rare and potentially damaging compound heterozygous variants were found in 27% of ALS patients, homozygous recessive variants in 14% and coding de novo variants in 27%. In 20% of patients more than one of the above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 49 publications
3
65
0
Order By: Relevance
“…This resulted in an average of 0.84 coding de novo mutations per trio, which is higher compared with previous studies in ALS with de novo mutation rates of 0.53 (Chesi et al., ) and 0.39 (Steinberg et al., ) (mean difference with previous studies combined 0.38, 95% confidence interval [CI] 0.14–0.62, P = 0.003), but consistent with the expected distribution in the general population (Samocha et al., ) (mean difference 0.14, 95% CI −0.06 to 0.34, P = 0.16).…”
Section: Resultssupporting
confidence: 84%
“…This resulted in an average of 0.84 coding de novo mutations per trio, which is higher compared with previous studies in ALS with de novo mutation rates of 0.53 (Chesi et al., ) and 0.39 (Steinberg et al., ) (mean difference with previous studies combined 0.38, 95% confidence interval [CI] 0.14–0.62, P = 0.003), but consistent with the expected distribution in the general population (Samocha et al., ) (mean difference 0.14, 95% CI −0.06 to 0.34, P = 0.16).…”
Section: Resultssupporting
confidence: 84%
“…This genetic association was not replicated in other studies (9,10). Although recent exome sequencing of case-unaffected–parents trios identified a de novo variant in ITPR2 (11), the potential role of this variant remains unclear. The higher ITPR2 gene expression in ALS also remains intriguing due to the important role of the gene product of ITPR2 , the inositol 1,4,5-trisphosphate receptor 2 ( IP 3 R2 ), in calcium signalling.…”
Section: Introductionmentioning
confidence: 99%
“…The results in patients' cells show increased transcription of NEDD4L, a gene encoding another E3 ubiquitin ligase targeting TSG101. 40 PLA2G4C encodes a membrane-bound phospholipase that hydrolyses glycerophospholipids into various signaling molecule precursors, 41 but its potential role in neurodegeneration has yet to be explored. Double knockout studies 36 have revealed that mutations in a functionally redundant gene often lead to a minor or no phenotype, whereas targeting the compensatory gene pair together substantially increases severity, for example, dystrophin and utrophin A in a mouse model of Duchenne muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%